Development of Porosity of Low Cost Activated Carbon from Post-Consumer Plastics and Lignocellulosic Waste Materials using Physico-Chemical Activation (Global Journal of Science Frontier Research, 2018)
Low-cost adsorbents (from Oil Palm Shell (OPS) and polyethyleneterephtalate (PET)) were prepared by physical activation with steam and Physico-chemical activation using both KOH and steam in the way to study the modification of porosity, pores size distribution and surface functional group. The activated samples obtained by physical activation are microporous with a surface area between 1000and 1500 m2/g, while the other obtained by physicochemical activation contain a well-developedporosity which consists of micropores, mesopores and likely macropores with a surface area between 991 and 1413 m2/g. The adsorption of methylene blue (MB) and iodine (I2) show that physicochemical activation produced a strongly developed internal surface, which is open at the surface by, mesopores and possibly macropores. FTIR spectrum of ACs prepared shows many peaks belonging to different functional groups.
Keywords: physicochemical activation; porosity; functional group; low-cost adsorbent; activated carbon